"Then There Was War:" John Hejduk's The Silent Witnesses as Nuclear Criticism. Issue 2 (4th May 2018) - Dorrian, Mark
Abstract: Drawing on the reflections contained in Roland Barthes' lectures on the "Neutral, " this article reconsiders John Hejduk's The Silent Witnesses installation (1976), often thought a peripheral work despite the architect's assertion that it is his most important statement. While discussions of silence normally presume the presence of a listener, I argue that this work concerns that which – if we can still describe it as silence – endures beyond any possibility of audition. This is the condition emblematized by the final blank gray volume of Hejduk's installation, whose radical erasure of all traces gestures toward the absolute archival destruction – characterized by Jacques Derrida as an "apocalypse without revelation" – presaged by the nuclear age.